Distributed Control Strategies for Microgrids: A Critical Review of Technologies and Challenges - Ghali Ahmad; Abdulbasit Hassan; Asif Islam; Md Shafiullah; Mohammad A. Abido; Mujahed Al-Dhaifallah (IEEE Access)
The surging growth of the global energy demand, rapid depletion of fuel reserves, and, most importantly, increasing global warming trends have been the major concerns for decision-makers for the last couple of decades. The current prevalent renewable and clean power sources such as wind, hydro, and solar energy provide workable solutions to the foregoing problems via (DGs). Microgrids (MGs) are essential for interfacing the major portion of renewable energy sources and decision-making regarding the control and operation modes. Recent MG research trends focused on integrating those affordable and cost-effective resources into the energy mix at a consumer level. Still, due to the complexity of DG integration into the MG, many research efforts have been made to examine and develop distributed control (DCT) systems for alternating current, direct current, and hybrid MGs, and adherents of this approach, the distributed controllers have numerous advantages compared with centralized and decentralized control methods, such as increased reliability, flexibility, controllability, possibility to initiate operations independently, and robustness to communication failures. This research critically reviews the DCT strategies developed for MGs, presents various MG control strategies, and delves into different approaches to designing distributed controllers. Besides, this article highlights existing challenges and possible ways of mitigation, most especially by using artificial intelligence approaches. It also reviews the multi-microgrid concept to shed light on modern technologies and their potential applications in MGs. It is expected that the decision-makers and the researchers will find the critical analysis of this article useful while delving into various control strategies for MG.